Define the star operation as a ⋆ b = a + a b + b .
Then define the star power operation as a ⋆ n = a w r i t t e n n t i m e s a ⋆ a ⋆ a ⋆ ⋯ ⋆ a , with a ⋆ 1 = a .
What is 7 ⋆ 7 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
to go from step 1 to step 2 you leap an assumpion that "star" is the same as "multiplacation"!! For here its treu, but you didn't proofed it!
Log in to reply
The step I left out is showing that the pattern continues with repeated multiplication:
( a ⋆ b ⋆ c ) + 1 : = ( ( a ⋆ b ) ⋆ c ) + 1 = ( ( a ⋆ b ) + 1 ) ( c + 1 ) = ( a + 1 ) ( b + 1 ) ( c + 1 ) ,
and so on.
Bammens is correct. You assume that this operation works same as multiplication.
Log in to reply
The observation I made is essentially that f : ( R − { − 1 } , ⋆ ) → ( R − { 0 } , ⋅ ) f : x ↦ x + 1 is a group isomorhpism.
The proof is that ( a ⋆ b ) + 1 = ( a + 1 ) ⋅ ( b + 1 ) .
A consequence is that ( a ⋆ b ⋆ ⋯ ⋆ z ) + 1 = ( a + 1 ) ⋅ ( b + 1 ) ⋅ ⋯ ⋅ ( z + 1 ) .
From the first few n , we find that a ⋆ n = ( a + 1 ) n − 1 . Let us prove by induction that the claim is true for all n ≥ 1 .
Proof: For n = 1 , a ⋆ 1 = ( a + 1 ) 1 − 1 = a as defined. Therefore, the claim is true for n = 1 . Now assuming that the claim is true for n , then we have:
a ⋆ ( n + 1 ) = a ⋆ a ⋆ n = a + a ( a ⋆ n ) + a ⋆ n = a + a ( ( a + 1 ) n − 1 ) + ( a + 1 ) n − 1 = a + a ( a + 1 ) n − a + ( a + 1 ) n − 1 = ( a + 1 ) n + 1 − 1 .
Therefore, the claim is also true for n + 1 and hence for all n ≥ 1 . Then we have 7 ⋆ 7 = ( 7 + 1 ) 7 − 1 = 2 0 9 7 1 5 1 .
Actually a way cleaner version of my solution, chapeau! :D
don't calculate it true, stop at 8(to the power)7 -1. Nice work
Log in to reply
The problem required the whole solution. It has been changed to a multiple choice some days ago
this is clean
We can see, with some counting, that the following formula holds (proof at the end):
a ⋆ n = k = 1 ∑ n ( k n ) a k
In particular, if a = 1 , we have
1 ⋆ n = k = 1 ∑ n ( k n ) = 2 n − 1
And since 7 = 2 3 − 1 = 1 ⋆ 3 , we have:
7 ⋆ 7 = ( 1 ⋆ 3 ) ⋆ 7 = 1 ⋆ 2 1 = 2 2 1 − 1 = 2 0 9 7 1 5 1
Note: Proof of the fact that ( 1 ⋆ 3 ) ⋆ 7 = 1 ⋆ 2 1 is left to the kind reader. Does this power property apply to every base or just to 1?
Now, as to why the star power formula holds. We are just going to prove this by induction. It is in fact obvious that the formula holds for n = 2 , as a ⋆ 2 = a ⋆ a = a 2 + 2 a = ( 2 2 ) a 2 + ( 1 2 ) a
Let's suppose that it holds for n and let's prove it for n + 1 .
a ⋆ ( n + 1 ) = a ⋆ n ⋆ a = ( k = 1 ∑ n ( k n ) a k ) ⋆ a = k = 1 ∑ n ( k n ) a k + a + a k = 1 ∑ n ( k n ) a k
= k = 1 ∑ n ( k n ) a k + k = 1 ∑ n ( k n ) a k + 1 + a
= k = 2 ∑ n ( k n ) a k + ( 1 n ) a + ( n n ) a n + 1 + k = 2 ∑ n ( k n ) a k + a
= k = 2 ∑ n [ ( k n ) + ( k − 1 n ) ] a k + ( n + 1 n + 1 ) a n + 1 + ( 1 n ) a + a
= ( n + 1 n + 1 ) a n + 1 + k = 2 ∑ n ( k n + 1 ) a k + ( 1 n + 1 ) a = k = 1 ∑ n + 1 ( k n + 1 ) a k
To proceed with these equalities we used some basic properties of the binomial coefficient and manipulation of the sums.
Instead of 7, use variable x, then:
These polynomials and the coefficients 1 , 4 , 6 , 4 look familiar! It's Pascal's triangle, whose rows contain the coefficients for binomial expansions ( a + b ) n . To make it fit the triangle's pattern, we choose a = x , b = 1 , n = 7 to arrive at ( x + 1 ) 7 − 1 .
With x = 7 , the answer is 8 7 − 1 .
Pascal Triangle, you meant.
While this works, programming solutions are not always a good idea as they don't give insight on the properties of the operation.
What does it matter? One may ask. Well, for more complex problems, efficiency of a program is a big issue. By applying the direct definition of star power, your program makes 3 n operations to calculate a ⋆ n , whereas you only need n + 2 because of the formula a ⋆ n = ( a + 1 ) n − 1 .
(Sorry not a solution) Everyone here is so smart. I feel like a total hyena for getting out my calculator and punching it out.
Log in to reply
Originally, the problem had an answer box, which allowed you to actually brute force the problem. This has been corrected by the mods with the multiple choice. I don't always like the idea of it, but in this case it doesn't allow brute-forcing anymore as your calculator/PC will give 2 0 9 7 1 5 1 as a result, but won't translate it as 8 7 − 1 .
Or with recursion..
def star(a, b):
return a + a*b + b
def starpower(a, n):
if n == 1:
return a
else:
return star(a, starpower(a, n - 1))
print(starpower(7, 7))
Problem Loading...
Note Loading...
Set Loading...
Complete the product: a + a b + b = ( a + 1 ) ( b + 1 ) − 1 . This suggests that ( a ⋆ b ) + 1 = ( a + 1 ) ( b + 1 ) , so that ( a ⋆ b ⋆ c ⋆ ⋯ ⋆ z ) + 1 = ( a + 1 ) ( b + 1 ) ( c + 1 ) ⋯ ( z + 1 ) , and a ⋆ n + 1 = ( a + 1 ) n . Thus 7 ⋆ 7 = ( 7 + 1 ) 7 − 1 = 8 7 − 1 .